2002
DOI: 10.17221/3513-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biochemical changes during microwave treatment of wheat

Abstract: Currently attention is paid to a possible use of microwave (MW) heating for the drying of cereal grain, rice or pulses. Heat from the kernel surface is transferred by conduction to the inner endosperm if the usual convention drying of grain with hot air is used. This method of drying is time consuming with low economic effectiveness since heat conductivity of wheat kernel is rather low, similarly to insulating materials. MW heating allows drying grains to a permitted limit moisture without deteriorating effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…This finding indicated that thermal denaturation of glutens in sound and damaged samples might be with different microwave times owing to having different levels of proteolytic activity in flours. The changes in WG content are similar to the findings previously reported by many authours (Doty and Baker 1977;MacArthur, 1981;Campaña et al, 1986Campaña et al, , 1993Lupano and Anón, 1987;Koksel et al, 1993;Türker and Elgün, 1998;Kaasov et al, 2002;Walde et al, 2002).…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…This finding indicated that thermal denaturation of glutens in sound and damaged samples might be with different microwave times owing to having different levels of proteolytic activity in flours. The changes in WG content are similar to the findings previously reported by many authours (Doty and Baker 1977;MacArthur, 1981;Campaña et al, 1986Campaña et al, , 1993Lupano and Anón, 1987;Koksel et al, 1993;Türker and Elgün, 1998;Kaasov et al, 2002;Walde et al, 2002).…”
Section: Methodssupporting
confidence: 89%
“…Also, these results in gluten index indicated improvement of dough elasticty and strengh due to the partial inactivation of excessive proteolytic activity from wheat bug enzyme and gluten strength development. The harsh gluten occuring by thermal process were reported by many authors (Koksel et al, 1993;Ugareiah and Hackenberger, 2001;Kaasov et al, 2002;Walde et al, 2002).…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…Most studies that dealt with the use of MW systems for the uses of food processing, including for rice drying and decontamination, have been laboratory-based experimentations that employed MW systems operated at 2,450 MHz frequency (Kaasova, Kadlec, Bubnik, Hubackova, & Prihoda, 2002;Kumar, 2015;Le, Songsermpong, Rumpagaporn, Suwanagul, & Wallapa, 2014;Liu, Jiaqiang, Deng, Xie, & Zhu, 2016a;Liu, Jiaqiang, Ma, & Xie, 2016b). However, there has been limited success in scaling up MW heating to dry rice with the frequency set at 2,450 MHz (Cho, Aoki, Miyatake, & Yoshizaki, 1990;Kaasova et al, 2002;Maskan, 2001;Prabhanjan, Ramaswamy, & Raghavan, 1995;Vadivambal & Jayas, 2007); this has been primarily due to the limitations on depth of penetration into the grain bed and hence occurrence of nonuniform heating across thick beds (Kumar, 2015).…”
Section: Introductionmentioning
confidence: 99%